93 Targeting sirt2 rescues the metabolic fitness and effector functions of tumor-reactive T cells within the metabolically restricted tumor microenvironment. (9th November 2020) - Hamaidi, Imene; Zhang, Lin; Kim, Nayoung; Wang, Min-Hsuan; Iclozan, Cristina; Fang, Bin; Liu, Min; Koomen, John; Berglund, Anders; Yoder, Sean; Yao, Jiqiang; Engelman, Robert; et al.
Abstract : Background: The majority of cancer patients remain refractory to existing cancer immunotherapies. Despite the growing evidence that dysregulated metabolism contributes to the exhaustion of tumor-infiltrating T lymphocytes (TILs) and the loss of their effector functions within the metabolically restricted tumor microenvironment (TME), actionable targets to rescue metabolic fitness and anti-tumor activity of TILs remain elusive.Memory T (TM) cells and TILs rely on fatty acid catabolism to preserve their effector functions due to nutrient competition for glucose with tumor cells. Therefore, enhancing fatty acid catabolism of TILs represents an attractive strategy to increase the efficacy of immunotherapies.Sirt2 is an NAD+ dependent histone deacetylase. We previously showed that upregulation of Sirt2 in human TILs negatively correlates with response to TIL therapy in advanced non-small cell lung cancer (NSCLC) and Sirt2 deficiency leads to hyper-reactive T cells with superior antitumor activity. Methods: Sirt2 expression was analyzed by flow cytometry and Western blot. The role of Sirt2 in tumor immunity was studied using in vivo B16F10 tumor challenge models as well as ex vivo analysis including RNA-sequencing, CFSE proliferation assay, DAPI/AnnexinV staining, IFN-γ ELISpot assay, intracellular staining of effector molecules and LDH cytotoxicity assay on WT versus Sirt2KO T cells. Molecular partners of Sirt2 were identified using mass spectrometry (MS) and Co-immunoprecipitation analyses. The role of Sirt2 in T cell metabolism was investigated using seahorse bioanalyzer and LC-MS/MS Metabolomic profiling. AGK2, a Sirt2 selective inhibitor, was used for Sirt2 blockade in human T cells. Results: Sirt2 expression is upregulated during T cell activation, TM stage, and within the TME. Our molecular studies revealed that Sirt2 negatively impacts the acetylation status and the activity of the trifunctional protein, the key enzyme of fatty acid oxidation (FAO). Accordingly, Sirt2 deficiency enhanced FAO and metabolic fitness of activated T cells and mouse TILs isolated from B16F10 tumor nodules. As a consequence of enhanced FAO, Sirt2 deficient mice displayed increased accumulation of TM cells, which was associated with decreased apoptosis and increased survival after tumor challenge leading to superior tumor rejection. Most importantly, pharmacologic inhibition of Sirt2 in human TILs isolated from NSCLC patients enhanced their metabolic fitness and cytotoxic activity against their autologous tumor cells. Conclusions: Our findings indicate Sirt2 as a suppressor of T cell metabolism amenable to therapeutic targeting, and Sirt2 inhibition reprograms T cell metabolic fitness to optimally sustain their effector function within the hypoglycemic TME, thus, leading to an effective anti-tumor immune response. Acknowledgements: This work was supported in part by K08 CA194273, ACS IRG-17-173-22, NCI Cancer Center Support Grant (P30-CA076292) and the Moffitt Foundation.